Obesity and academic performances in adolescents - Nina Herlina; Julistio TB Djais; Kusnandi Rusmil (Paediatrica Indonesiana, 2013)
Background Adolescence is a phase of dynamic developmentin human life, marked by rapid physical growth, in addition tomental, emotional, and social development. Adolescent obesityhas been related to metabolic disease, in addition to psychologicaldisorders, which may lead to a negative impact on academicperformances.Objective To assess academic performances in adolescents withobesityMethods A cross-sectional study was conducted in Junior HighSchool No. 14 in Bandung from December 2010 to July 2011.Subjects were aged 12 to 14 years, and were divided into two groups:obese or good nutritional status. Statistical analysis using Fisher'sexact test was performed to assess the association of obesity andacademic performances. T-test was used to compare subjects' meanmathematics and English performances in the two groups.Results There were 24D students who met the inclusion criteria.Since there were 40 obese subjects in the first group, we randomizedthe remaining students to obtain 40 subjects with good nutritionalstatus for the second group. Best academic performances inmathematics and English was obtained mostly by subjects in thegood nutrition group (38/40 and 39/40, respectively). Statisticalanalysis revealed a significant association of lower performances inmathematics (mean difference -2.8; 95%CI -5 to -0.6; P=0.043)and English (mean difference -1.9; 95%CI -3.5 to -0.2; P=0.001)to obesity. We also found a significant association of bettermathematics (P=0.001) and English performances (P=0.004)to the father's occupation. Additional English lessons were notassociated with higher English performances in the obese group(mean difference 0.2; 95%CI -2.9 to 3 .2; P=0.885).Conclusion Obese adolescents tend to have poorer academicperformances compared to those with good nutritional status.